Active vibration control of horizontal-axis wind turbine blades using disturbance observer-based boundary control approach. (15th January 2023) - Jokar, H.; Vatankhah, R.; Mahzoon, M.
Highlights: Four active tendons mounted on the tip of the blade for the purpose of active vibration control. A new disturbance observer for estimation of the boundary disturbance. Boundary control design for vibration suppression of HAWT blades under distributed and boundary disturbances. Prove the stability of the closed-loop system using Lyapunov direct approach. Investigating the response of closed-loop system under wind shear inflow. Abstract: This paper addresses the issue of controlling vibration in horizontal-axis wind turbine (HAWT) blades under unknown boundary and distributed disturbances using an observer-based boundary control approach. In this regard, an actuator configuration, involving four active tendons mounted on the tip of the blade, is proposed to generate the out-of-plane and in-plane boundary control forces. The out-of-plane and in-plane governing equations are given as a set of PDEs and ODEs under parametric and direct excitations using Rayleigh beam theory including rotary inertia. A new disturbance observer is introduced to estimate boundary disturbances and subsequently combined with a new boundary control law for alleviating the HAWT blade vibration in the presence of unknown but bounded distributed disturbances. The uniform boundedness of the closed-loop system under unknown bounded distributed disturbances is confirmed via employing the Lyapunov's direct method together with LaSalle–Yoshizawa's theorem. Moreover, it is proved that the closed-loop system is uniformly exponentially stable in the absence of distributed and boundary disturbances. The reference NREL 5 MW HAWT blade is selected as the case study and the blade element momentum theory (BEMT) is employed to compute the aerodynamic load. Then, the open-loop and closed-loop responses of the blade under wind shear inflow and a predefined boundary disturbance are compared to demonstrate the performance of the closed-loop system in operational conditions.